Four species of Anomalon Panzer, 1804 (Hymenoptera: Ichneumonidae) newly recorded for Peru - Alvarado, Mabel (2014)
Four species of the parasitoid wasp genus Anomalon Panzer are recorded for the first time in Peru – Anomalon cotoi Gauld & Bradshaw, 1997, Anomalon duniae Gauld & Bradshaw, 1997, Anomalon fuscipes (Cameron, 1886), and Anomalon sinuatum (Morley, 1912).